2012
DOI: 10.1590/s0037-86822012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in a population exposed to occupational hazards: firefighters of a metropolitan region in central Brazil

Abstract: Introduction: By the nature of their activities, firefighters are exposed to a high risk of contracting hepatitis B virus (HBV) as most of the Fire Brigade occurrences in Campo Grande, State of Mato Grosso do Sul (MS), Brazil, are related to the rescue of victims of traffic accidents and the transportation of clinical and psychiatric emergencies. The aim of this study was to investigate the seroepidemiological profile of HBV infection in firefighters from the City of Campo Grande, central Brazil. Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
0
12
1
1
Order By: Relevance
“…The results observed in this profession in our study are higher than those reported in this field in Europe or in the United States, where the figures varied from 1% to 3% [11] [12] [13]. In sub-Saharan countries, no study has been made in this profession.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The results observed in this profession in our study are higher than those reported in this field in Europe or in the United States, where the figures varied from 1% to 3% [11] [12] [13]. In sub-Saharan countries, no study has been made in this profession.…”
Section: Discussioncontrasting
confidence: 89%
“…The prevalence of hepatitis B and C in the only sector of activity chosen in our study exposing professionally to the hepatitis viruses, the firefighters, has been the subject of many studies [11] [12] [13]. The results observed in this profession in our study are higher than those reported in this field in Europe or in the United States, where the figures varied from 1% to 3% [11] [12] [13].…”
Section: Discussionmentioning
confidence: 53%
“…The same rate of HBV immunity was observed among air force personnel from South Brazil, 17 but this rate is lower than the rate reported among Saudi Arabia soldiers (57.5%), fire-fighters from Central Brazil (66.9%), Spanish military personnel (78.3%). 13,18,19 Nowadays the coverage of hepatitis B vaccination among children less than 18 months of age varies from 80 to 95%, 16 but the low prevalence of HBV immunity observed in the present study is probably due to the fact they were the first generation of compulsory vaccination.…”
Section: Discussionmentioning
confidence: 50%
“…A prevalência global de infecção pelo HBV de 11,6% desta pesquisa foi duas vezes maior do que a prevalência encontrada em um estudo de base populacional, também realizado na Região Centro-Oeste, cuja prevalência global para infecção pelo HBV foi de 5,3% 14 . Estudos conduzidos no estado do Mato Grosso do Sul, com diferentes categorias profissionais expostas ao risco de infecção pelo HBV, encontraram resultados inferiores 15,16 . Este dado sugere que o exercício da enfermagem em ambiente hospitalar constitui fator associado ao risco de infecção ocupacional pelo HBV, provavelmente devido ao maior número de procedimentos invasivos de riscos realizados em situação de rotina e de emergência, maior tempo de permanência junto ao paciente e alta frequência de exposição aos fluidos corpóreos potencialmente contaminados pelo HBV.…”
Section: Infecção Pelo Hbv E Fatores De Riscos Associadosunclassified